2022
DOI: 10.3390/nu14061244
|View full text |Cite
|
Sign up to set email alerts
|

Association between Telomere Length and Pediatric Obesity: A Systematic Review

Abstract: Objective: Telomere length (TL) is a robust marker of biological aging, and increased telomere attrition is noted in adults with obesity. The primary objective of this systematic review was to summarize current knowledge on the effects of childhood obesity in TL. The secondary objective was to assess the effect of weight management interventions in TL. Methods: The following databases were searched: PubMed, Scopus, Web of Science and Heal-link.gr from inception to September 2021. The search was performed using… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 159 publications
(285 reference statements)
0
6
0
Order By: Relevance
“…However, there are other biological processes related to gene expression and the nervous system, which have smaller P-values relative to metabolism-related biological processes. Among them telomere organisation may be related to obesity, and it has been shown that telomere length is a strong marker of biological aging and increased telomere wear has been noted in obese adults [31]. The rest of the biological processes have not been found to be associated with obesity or BMI at this time, which provides new research directions and ideas for understanding the causes of obesity.…”
Section: Resultsmentioning
confidence: 99%
“…However, there are other biological processes related to gene expression and the nervous system, which have smaller P-values relative to metabolism-related biological processes. Among them telomere organisation may be related to obesity, and it has been shown that telomere length is a strong marker of biological aging and increased telomere wear has been noted in obese adults [31]. The rest of the biological processes have not been found to be associated with obesity or BMI at this time, which provides new research directions and ideas for understanding the causes of obesity.…”
Section: Resultsmentioning
confidence: 99%
“…This increase of spermatozoa telomere length leads to an increase of telomere length in embryos as well as inborn children. This parameter can confer a real advantage in terms of protection against some diseases like obesity 107,108 . Furthermore, the telomere length in children's chromosomes is strongly associated with the sperm telomere length 6 .…”
Section: Discussionmentioning
confidence: 99%
“…This parameter can confer a real advantage in terms of protection against some diseases like obesity. 107,108 Furthermore, the telomere length in children's chromosomes is strongly associated with the sperm telomere length. 6 Considering that long telomere could predispose to cancer development, the association of advanced paternal age and risk of cancer in offspring has been explored.…”
Section: Discussionmentioning
confidence: 99%
“…[11] Studies have found that adults with obesity have been discovered to suffer from increased telomere attrition. [12] There is a negative association between obesity and telomere length. [13,14] While a higher BMI has been observed to be associated with shorter telomere length, [15] there is currently no scientific literature on the potential connection between WWI and telomere length.…”
Section: The Research Was Funded By the Medical Science And Technolog...mentioning
confidence: 99%